Perempuan Papua sebagai Penjaga Warisan: Peran Perpustakaan dalam Memberdayakan Pengrajin Noken - Vauziah, Siva (DIWANGKARA: Jurnal Pendidikan, Bahasa, Sastra dan Budaya Jawa, 2025)
Noken is a traditional bag made of woven natural fibers that symbolizes the identity and culture of the Papuan people. This bag can be used to carry garden products, as well as carry cultural values that live in the culture. However, the preservation of noken is hampered by various obstacles, including the commodification of noken that makes people see cultural value only as financial gain, as well as the lack of facilities and support needed to maintain traditional skills. This paper aims to explain the role of women in maintaining the tradition of noken making and the library's contribution in overcoming these obstacles. It is hoped that collaboration between libraries and women noken artisans can lead to better results for the preservation of traditional noken.